Shift Share Analysis to Determine Regional Economic Performance of Gorontalo - Silviana Taniu; Anggita Permata Yakup; Moh Arif Novriansyah (Gorontalo Development Review, 2020)
This article aims to analyze the economy of regencies and cities in Gorontalo Province. The research methodology used is to use Shift Share analysis to analyze components in determining the growth of economies in the regency and cities in Gorontalo Province in 2010-2019 obtained from Regency / City BPS in Gorontalo. The results of the study showed economic growth in Gorontalo City and Gorontalo Regency including growing rapidly, and Pohuwato Regency, Bone Bolango Regency, North Gorontalo Regency, and Boalemo Regency grew slowly, that districts/cities have different regional potential so that they still need support for development policies Furthermore and equalization of the Gorontalo Regional Government.